Wolff-Parkinson-White syndrome in a young infant - Cueva Parra, Angel David (2020)
Wolff Parkinson White Syndrome occurs due to the presence of accessory pathways that abnormally communicate the atria with the ventricles. It is one of the main causes of paroxysmal supraventricular tachycardia in young people and adolescents, in whom the ideal management is catheter ablation. This syndrome can also occur in younger patients such as neonates and infants, where the therapeutic options are different. We present the case of a 47-day-old patient who was admitted to a public pediatric hospital in Peru due to vomiting. Upon admission, she showed a heart rate of 250 beats per minute; wide QRS complex tachycardia was documented; later, on the electrocardiogram in sinus rhythm, signs of pre-excitation were evident.